The LAW index as an accurate indicator of the initiation of antiviral treatment in patients with chronic hepatitis B. Issue 1 (January 2017) - Lee, Jae Min; Seo, Yeon Seok; Kim, Tae Hyung; Ahn, Jem Ma; Yim, Sun Young; Kim, Seung Up; Jung, Young Kul; Kim, Ji Hoon; An, Hyunggin; Yim, Hyung Joon; Yeon, Jong Eun; Lee, Hong Sik; et al.
Abstract: Background and Aim: Considering that inflammation and fibrosis are major factors for the indication of antiviral treatment, liver stiffness measurements could help identify patients who require antiviral treatment. This study evaluated factors that best identify patients who require antiviral treatment and to develop a new indicator for chronic hepatitis B (CHB). Methods: Patients with CHB were randomly classified into a training or validation group, and a model for predicting necroinflammatory activity ≥ A3 or fibrosis grade ≥ F2 (A3F2) was established in the training group using binary regression analysis and validated in the validation group. Predictive efficacy was compared using area under the receiver‐operating characteristics curve analysis. Results: Four‐hundred ninety‐two patients were enrolled. In the training group, female sex, aspartate aminotransferase‐to‐platelet count ratio index (APRI), and liver stiffness were independent predictors of A3F2 on multivariate analysis. These variables were used to construct a novel model, called the LAW (liver stiffness, APRI, woman) index, as follows: 1.5 × liver stiffness value (kPa) + 3.9 × APRI + 3.2 if female. The LAW index was a better predictor of A3F2 than the APRI or liver stiffness measurement in both training group (0.870; 95% confidence interval, 0.822–0.910) and validation group (0.862; 95% confidence interval, 0.813–0.903). Conclusions: The LAW index was able to accurately identify patients with CHB who required antiviral treatment. A LAW index of >10.1 could be a strong indicator for the initiation of antiviral treatment in patients with CHB.